Training Upaya Berhenti Merokok Guru Pembina Unit Kesehatan Sekolah Tingkat SLTP di Kabupaten Pandeglang Banten Tahun 2024 - Siti Nur Ramdaniati; Lambang Satria Himawan; E.Egriana Handayani; Erma Noor Wahyuningsih; Heny Sasmita; Ucu Wandi Somantri (STIKES Columbia Asia Medan, 2025)
Smoking can cause socio-economic problems, health issues, and even death. The activity aims to improve the understanding and skills of UKS mentor teachers about the importance of smoke-free areas (KTR) and smoking cessation efforts in schools, as well as follow-up on the implementation of KTR in schools with the Public Health Center. The intervention was carried out through a one-day training with lecture and question-and-answer discussion methods. The target of this activity was UKS mentor teachers at the junior high school level and PTM officers from the Public Health Center as many as 32 participants. The results of the activity: 1. Increased knowledge and awareness of teachers about the negative impacts of smoking on health, as well as creating a smoke-free environment in schools. 2. Changes in attitudes and behavior with a commitment from teachers not to smoke and strengthening the smoke-free policy program. 3. Increased student involvement in peer support programs for anti-smoking campaigns in the school environment. 4. Establishing cooperation between schools, parents, communities, and health agencies to create an environment that supports a healthy lifestyle. 5. The existence of a monitoring and evaluation system for student development in avoiding smoking and the impact of the UBM program in the school environment. 6. Improved health and quality of life by reducing the number of students and teachers who smoke, thereby creating a healthier and more conducive school environment for learning. These impacts are expected to contribute to efforts to improve health and well-being in the school environment and build a healthy living culture among students and staff.